Intelligent validation and establishment of homestay sustainability development indicators: Multidimensional verification based on multivariate analysis - Wan Abd Aziz, Wan Mohd Amin; Yahaya, Ibrahim; Ahmad Puad, Mat Som; Hawa Husna, Ab Ghani; A. B. H. M., Maliki; Mohd Shoki, Md Ariff (Serials Publications, 2017)
: This study aims to examine the structure and the validity of homestay sustainable development indicators in Malaysia. The participants were 359 homestay operators from registered homestay under Ministry of Tourism and Culture. A set of the semi-structured questionnaire were distributed, and the data set completed analyzed with EFA to obtain the appropriate model for homestay sustainability development. Then, a series of CFA was conducted, targeting to cross-validate the result obtain from EFA analysis. This study postulates suggestion of the reliability and validity of local leadership, community participation, organizational capacity, branding, environmental, socio-economy and government support as homestay sustainability development indicators.